The Impact of Credit Ratings on Firms’ Capital Structure - Feda, Rana Abdelhafeez (International Journal of Economics and Financial Issues, 2020)
In today’s financial markets, credit ratings play a significant role on the creditworthiness of firms as it represents the ability of a firm paying back debt and firm’s risk of default. The purpose of this study is to empirically evaluate the impact of credit ratings on firms leverage decisions. This paper examines firms leverage behavior with the discrete benefits of higher credit rating hypothesis presented by Kisgen (2009). The empirical tests were designed based on the Partial Adjustment Model by Flannery and Rangan (2006). Firms that have faced a downgrade are more likely to reduce their financial leverage by reducing debts and issuing equity, with conscious of the costs of doing so. While firms that been upgraded from speculative grade to investment grade do little changes in their capital structure to maintain the discrete benefits attributable to higher credit ratings. The results of this paper are persisted with CR-CS hypothesis. Keywords: Financial Markets, Credit, Debt Management, Firm Performance, Capital Investment JEL Classifications: D53, E51, H63, L25, O16 DOI: https://doi.org/10.32479/ijefi.10436